ERGONOMIC ANALYSIS IN COAT OF COATINGS IN GRAFIATO (Fiep Bulletin - online, 2014)
The construction industry has proved of great importance to the national economy and for job creation. However, the sector is also responsible for a large number of accidents at work and occupational diseases, which shows that the concern with ergonomics is still very superficial. Thus, this research presents an ergonomic analysis of the workplace for the frontage cladding of buildings. The activity is carried out by painters, which run texture finish, named “grafiato”. For the analysis, two different construction sites were visited, being the work - named "work I" - executed by a large construction company, and the work entitled "work II" performed by a smaller enterprise, both in the city of Curitiba, state of Paraná, Brazil. Therefore, the officials regarding this activity were interviewed to identify biomechanical problems resulting from the job in question. The results showed that more experienced employees feel pain more intense, and in concentrated body areas; and that inexperienced staff feel pain in several regions, but with less intensity. In addition, the body area that suffers more with the activity in question is the shoulder. Thus, it can be concluded that the analyzed companies should incentive plan gymnastics at construction sites.
Keywords: Biomechanics; Ergonomic Analysis; Facade